Ultrafine Bubbles Technology for Breaking Dormancy of Sandalwood Seeds (Santalum album L. - Juliana Maia; Abdul Qadir; Eny Widajati; Yohannes Aris Purwanto (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2021)
Sandalwood seed has two types of dormancy, namely physical dormancy and physiological dormancy which is a combination of the Two-part is called morphophysiological dormancy. There is for breaks dormancy in sandalwood for earlier embryo maturation and elongation also it has hard and impermeable skin. Its structure consists of layers of thick-walled palisade-like cells especially on the outermost surface and the inside has a waxy coating and curse material. The objective of this study was to break of seed dormancy with technology Ultrafine Bubbles (UFB) on the morphophysiological dormancy on sandalwood seeds. The experiments used a randomized complete block designed (RCBD) with 3 replications. The data were analyzed using ANOVA and will be continued using the DMRT test at the 5% level. The research was conducted from February - March 0f 2020. The results showed that immersion using UFB water with oxygen 20 ppm or either UFB free oxygen for 24 and 48 hours combined with physical scarification and chemical scarification could accelerate germination in 13 days after germination (appeared radicle), percentage of growth speed (GS) is 4.67%, maximum growth (MG) in 21 days after sowing is 66.67% with normal sprouts 2-4 leaves have grown.